Exhibiting Reform: MoMA and the Display of Public Housing (1932–1939). Issue 1 (11th September 2018) - Woudstra, Rixt
Abstract : While the explicit aestheticization of modern architecture during MoMA's first decade of exhibitions is well known, it is too often forgotten that this interpretation was countered from the beginning by exhibitions advancing an understanding of architecture that emphasized its social effects. Coinciding with America's first large-scale public housing projects, part of the New Deal's attempt to end the Great Depression through relief, recovery, and reform, MoMA installed several shows advocating for public housing during the 1930s — an overlooked facet of the museum's well-documented history. This article explores how MoMA was instrumental in introducing and promoting the concept of public housing to the American public by cooperating on several exhibitions with local and federal public housing authorities, such as Housing Exhibition of the City of New York (1934), Architecture and Government Housing (1936) and Houses and Housing (1939). Figures involved in several of these exhibitions such as self-acclaimed 'housing expert' Catherine Bauer were also active as part of governmental and non-governmental housing organizations, creating the laws that radically reformed housing in the United States. And yet, these exhibitions simultaneously presented housing as a distinct subcategory of architecture — a category in which quantity and affordability were valued over excellent design. The housing exhibitions made the living environments of the poor visible but perpetuated the divide between a prized elitist modernized aesthetics and built environments for the working-class masses.